BOD characteristics and firm performances: Evidence from Indonesia - Muhammad Taufik; Louisky Chua (Universitas Sebelas Maret, 2021)
This paper investigates the relationship between gender diversity in BOD, BOD size, BOD independence, BOD meeting, BOD tenure, BOD turnover, and BOD remuneration to financial performances. This research is an empirical analysis using stewardship theory, which underlies BOD represents as stewards and tends to be pro-organization. The research sample is a company listed on the Indonesia Stock Exchange for the 2016-2019 period which consists of 237 companies and 940 observations. It is revealed that BOD size and BOD remuneration positively and significantly affect sales or business volume, ROA, and ROE. In contrast, gender diversity in BOD and BOD independence is considered unable to become stewards because companies and regulators did not accommodate those. BOD meetings, BOD tenure, and BOD turnover do not affect financial performance. We contribute to giving empirical reason to the government to accommodate the existence of female BOD and BOD independence in regulation and give suggestions to companies to evaluate the tenure of directors and the recruitment system. This paper also found an optimal BOD size which might be used as a reference for regulatory changes.